Empowering the Next Generation: A Framework for Developing Young Educators in Chinese Vocational Colleges - Wang Yixuan; Aminuddin Hassan; Nur Aimi Nasuha Binti Burhanuddin (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper examines the pivotal role of young teachers in the development of higher vocational education in China, set against the backdrop of the country’s rapid industrialization and technological evolution. It introduces a comprehensive index system designed to cultivate these educators by identifying key indicators of effectiveness, benchmarks for professional development, and necessary support mechanisms. Through a mixed-methods research approach, including surveys, interviews, and document analysis, the study presents a multi-dimensional framework emphasizing professional development, pedagogical skills, industry collaboration, and innovation. Case studies from urban, rural, and specialized vocational colleges illustrate the system's adaptability and impact, highlighting improvements in teaching quality and relevance. The paper concludes with recommendations for vocational colleges, policymakers, and directi ons for future research, emphasizing the importance of digital literacy, structured industry engagement, and the fostering of a culture of innovation to enhance the professional growth of young teachers and align vocational education with industry demands.